Beliefs in God and Religious Principles of Thinaikudis - N, Vennila (Indian Journal of Multilingual Research and Development, 2023)
The Primitive people's principles on God and religion and the religious principles came into being by the arrival of the Aryans were found in the ancient human society. Placing tombstone for dead is a significant ritual in Tamil tradition. This ritual marks the beginning of worship. It seems that the practice of placing tombstone was before the time of Tolkappiyar. The ancient people believed in ghosts and believed that there was a deity under the tree. Idol worship was also significant among ancient peoples. It is also proved that people of Harappa Mohanjataro worshiped Shiva Linga. KK Pillai says that this worship is a form of Palkuri worship, and if research confirms that Tamil people belong to this ancient culture, Palkuri worship has existed among Tamil people thousands of years ago. Ancient Tamil worship is the forerunner of today's religious doctrine. Due to Vedic influence there have been changes in religious tradition. The religious doctrine of the ancient Hindus was completely outside the Vedic scriptures. The deity symbols of the Thinaikudis are a reflection of the caste. It indicates the status of ancestor worship. The gods were felt to be present in the house, as life companions.